A Late Cretaceous mixed (turbidite-contourite) system along the Argentine Margin: Paleoceanographic and conceptual implications. (January 2021) - Rodrigues, S.; Hernández-Molina, F.J.; Kirby, A.
Abstract: The Late Cretaceous record offshore Argentina comprises an extensive mixed (turbidite-contourite) depositional system over 280, 000 km 2 . This offers a key site to investigate complex assemblages of morphosedimentary features and their depositional processes during one of the major tectonic events in the southern hemisphere: the breakup of Gondwana (125 Ma) and the opening of the South Atlantic Ocean. The mixed depositional system was studied using a new 2D multichannel seismic reflection dataset and well data. This system developed along the continental slope and rise between 3500 and 6500 m SSL with nineteen 300–500 m thick, mounded drifts, separated by sixteen 2–5 km wide submarine channels. Seismic interpretation and correlations suggest four main evolutionary stages: a) the pre-drift stage (~125–89.8 Ma) from the Aptian to the Coniacian marks thermal subsidence of the margin followed by initiation of a turbidite depositional system; b) the onset stage (~89.8–81 Ma) from the Coniacian to the Campanian records the first exchange between SE turbidity flows and weak SW bottom currents; c) the growth stage (~81–66 Ma) records maximum growth from the Campanian to the Maastrichtian, characterized by the SW progradation and expansion of the mixed system due to more frequent interactions between turbidity and alongslope bottom currents; and d) the burial stage (~66 Ma) marks the cessation of the mixed system in the Paleocene due to bottom current intensification and transition to a pure contourite system, which persists until the present day. These four evolutionary phases register the Mesozoic to Cenozoic paleoceanographic fluctuations, associated with the northward opening of the South Atlantic Ocean and the establishment of a new deep-water circulation regime. Control factors for this mixed depositional system link inherited morphological structures, regional tectonic events, a mutable oceanic circulation, and recurrent gravity-driven processes. The present results were also compared with other mixed systems of similar or different geological age to contextualize the paleoceanographic and conceptual implications for deep-marine sedimentary environments. This comparison allowed us to identify two end members of drift and channel migration (upstream versus downstream), differentiated by the dominance of alongslope bottom currents vs. downslope turbidity currents. The distribution of the morphological elements and their lateral migration reflects the imprint of the most influential process and the changing energy, velocity, frequency and timing between the two processes. A future challenge will be to determine the full spectrum of mixed/hybrid systems, from turbidite-dominated to contourite-dominated settings, and how they differ vertically and spatially in the sedimentary record. Highlights: Hybrid turbidite-contourite depositional system along the Argentine Margin. Coeval interaction between alongslope and downslope processes. Hybrid deposits will reflect the imprint of the most influential and energetic process. Long-term transition from a margin dominated by gravity flows to bottom-currents. Establishment of new intermediate and deep-water circulation by the Late Cretaceous.